I am Helen Keller - Norwich, Grace; Elliot, Mark (New York : Scholastic, 2012)
A biography of deaf and blind human rights activist Helen Keller.
Includes biographical references (p. 125) and index.
6.9
3-6
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Deafblind people -- United States -- Biography -- Juvenile literature; Keller, Helen, -- 1880-1968.; Deafblind people -- Biography; Women -- Biography; Keller, Helen, -- 1880-1968.; Handicapped -- United States -- Biography; Women -- Biography